The defect detection in ceramic materials based on wavelet analysis by using the method of impulse noise - (:unkn) unknown (JVE INT LTD, 2013)
In this experimental study, it was achieved to detect internal or surface cracks that can occur in the production of ceramic plates by using the method of impulse noise. This method is a test technique which was not used in the applications. In this experimental study, a pulse is applied on the ceramic material. This pulse is produced by pendulum mechanism. With the reflected sound material, the deformation of the material is analyzed. The application of the study was performed on ceramic plates. Ceramic double plates, made from same materials, with same characteristics, but in different models, were used. One of these ceramic double plates, both of which are entirely of the same kind, is un-deformed plate, and the other is cracked plate. Impulse noises, having arisen from the equal impulse power applied on these intact and cracked plates of the same model, were examined by wavelet analysis. By means of the applied method, it was seen to have shown significant results in distinguishing intact and cracked plates. Having the frequency and magnitude dimensions of the deformations on the plates also examined by means of the applied analysis, important distinguishing findings were attained therefrom.
Keywords: sound vibration; impulse noise; continuous wavelet analysis; defect detection in ceramics materials; ACOUSTIC-EMISSION